Dinamika Kelas Sosial Dalam Novel Home Sweet Loan Karya Almira Bastari: Teori Karl Marx - Afifah Syifa’ul Qolbi; Titik Indarti (CV. SINAR HOWUHOWU, 2026)
This study aims to describe the dynamics of social class in the novel Home Sweet Loan by Almira Bastari based on Karl Marx’s theory, which includes social class dynamics, forms of exploitation, and forms of alienation. This research employed a descriptive qualitative approach. The data source was the novel, while the research data consisted of words, phrases, sentences, and dialogues that reflected social class phenomena in urban society. Data techniques were collected use reading and note-taking techniques. Data analysis was conducted through the stages of data reduction, data presentation, and conclusion drawing. The results of the study revealed into three main aspects namely social class, exploitation, and alienation. From Karl Marx’s perspective, these phenomena indicate that the capitalist system not only produces economic inequality but also creates exploitation and alienation that affect the social life of urban communities. Through its representation of the characters’ lives, the novel Home Sweet Loan presents a social critique of the realities faced by the middle class under economic pressures and social demands within modern capitalist social.